A Novel Optical Thermometry Strategy Based on Diverse Thermal Response from Two Intervalence Charge Transfer States. (24th February 2016) - Gao, Yan; Huang, Feng; Lin, Hang; Zhou, Jiangcong; Xu, Ju; Wang, Yuansheng
Abstract : In this work, a novel thermometry strategy based on the diversity in thermal quenching behavior of two intervalence charge transfer (IVCT) states in oxide crystals is proposed, which provides a promising route to design self‐referencing optical temperature sensing material with superior temperature sensitivity and signal discriminability. Following this strategy, uniform Tb 3+ /Pr 3+ :NaGd(MoO4 )2 micro‐octahedrons are directionally synthesized. Originated from the diverse thermal responses between Tb 3+ ‐Mo 6+ and Pr 3+ ‐Mo 6+ IVCT states, fluorescence intensity ratio of Pr 3+ to Tb 3+ in this material displays excellent temperature sensing property in a temperature range from 303 to 483 K. The maximum absolute and relative sensitivity reaches as high as 0.097 K −1 and 2.05% K −1, respectively, being much higher than those of the previously reported optical thermometric materials. Excellent temperature sensing features are also demonstrated in the other Tb 3+ /Pr 3+ codoped oxide crystals having d 0 electron configured transition metal ions (Ti 4+, V 5+, Mo 6+, or W 6+ ), such as scheelite NaLu(MoO4 )2 and NaLu(WO4 )2, and monazite LaVO4 and perovskite La2 Ti3 O9, evidencing the universal validity of the proposed strategy. This work exploits an effective pathway for developing new optical temperature sensing materials with high performance. Abstract : A novel thermometry strategy based on the diversity in thermal quenching behavior of two intervalence charge transfer states is proposed in this work. Following this strategy, several self‐referencing optical temperature sensing materials with excellent performance are fabricated.